Insuficiencia renal crónica - Naula Dominguez, Valeria Stefany; Pauta Miro Monica Elizabeth (Machala : Universidad Técnica de Machala, 2019)
Chronic Renal Insufficiency (CRF) is a progressive, degenerative and irreversible disease that results in the inability of the kidneys to filter toxic substances from the blood, regulating excess fluid, causing a glomerular decrease of less than 60 ml / min / 1.73 m2 within the normal parameters, which lead to irreversible renal failure for three or more months, which carries a higher risk of morbidity and mortality in the place of frequent practice such as arterial hypertension as the main cause, then as we have Type Diabetes Mellitus II and Dyslipidemia. The objective of this case analysis is the application of the nursing care process through an exhaustive evaluation of the 14 basic practices of Virginia Henderson, in a geriatric patient with chronic renal failure, based on the review of the clinical history and the articles. For the prevention of this pathology there are the levels of attention; the environment that includes the promotion of health for the purpose of educating the population about the diseases that can be associated with the consumption of alcohol, tobacco and a diet rich in fats, salt and sugar; and the protection one has to carry out activities that promote good physical and mental functioning. At the secondary level, it is carried out through early diagnosis, timely treatment and limitation of damage; at the tertiary level it includes rehabilitation to improve or maintain a timely state of health. The problem is found in the Chronic Renal Insufficiency that was evidenced in an 88-year-old patient in Machala General Hospital in the second semester of 2017. The type of research to be used is the qualitative method, it is not about the quality of the activities, relationships, issues, means, materials or instruments in a certain situation or problem, the same that we improve in a profound way and study the phenomena from multiple perspectives of the unit of analysis.In addition, instruments were used to collect information that were based on legal ethical aspects that helped to provide the patient's medical history more easily; this was the request addressed to the Machala General Hospital to Doctor Leonardo Alvarado, medical deputy director, a preliminary project was presented that framed the informed consent. As a result, it was obtained that the patient through the performance of different studies establishes the diagnosis of Chronic Renal Insufficiency. The patient received as basic treatment: Simvastatin; Tamsulosin and Haloperidol. We conclude that Chronic Renal Insufficiency is one of the pathologies frequently worldwide according to the WHO. In this investigation according to the case study the patient presents Chronic Renal Insufficiency which affects the quality of life of the individual because they can not have a good proper management of their treatment; for these reasons, prevention measures must be put in place. The changes suffered by the patient diagnosed with CRI are multiple, including at the family, social, personal and economic level. The interventions of the nursing staff constitute a fundamental pillar when facing and accepting precarious situations through which the patient passes.
La Insuficiencia Renal Crónica (IRC) es una enfermedad progresiva, degenerativa e irreversible que tiene como consecuencia la incapacidad de los riñones para filtrar sustancias toxicas de la sangre, regulando el exceso de líquidos, provocando una disminución de filtración glomerular inferior a 60 ml/min/1.73 m2 dentro de los parámetros normales, que conduce un fallo renal irreversible durante tres o más meses, que conlleva un mayor riesgo de morbimortalidad dando lugar a complicaciones clínicas frecuentes como la Hipertensión Arterial como la principal causa, luego como consiguiente tenemos la Diabetes Mellitus Tipo II y Dislipidemia considerada un problema de salud a nivel mundial. El objetivo del presente análisis de caso es aplicar el proceso de atención de enfermería mediante una valoración exhaustiva de las 14 necesidades básicas establecidas por Virginia Henderson, en un paciente geriátrico con Insuficiencia Renal Crónica, basado en la revisión de la historia clínica y artículos científicos. Para la prevención de esta patología existen tres niveles de atención; el primario que comprende la promoción de la salud con el fin de educar a la población sobre las enfermedades que pueden asociarse por el consumo de alcohol, tabaco y una alimentación rica en grasas, sal y azúcar; y la protección específica encargado de realizar actividades que promuevan el buen funcionamiento físico y mental. En el nivel secundario se realiza mediante un diagnostico precoz, tratamiento oportuno y limitación del daño; en el nivel terciario comprende la rehabilitación para mejorar o mantener un estado de salud oportuno. La problemática hallada es la Insuficiencia Renal Crónica que se evidencio en un paciente de 88 años de edad atendido en el Hospital General Machala en el segundo semestre del 2017. El tipo de investigación a utilizar es el método cualitativo, nos permiten estudiar la calidad de las actividades, relaciones, asuntos, medios, materiales o instrumentos en una determinada situación o problema, la misma que permiten explorar de forma profunda y estudiar los fenómenos desde múltiples perspectivas de la unidad de análisis. Además se utilizó instrumentos para la recogida de información que se basaron en aspectos éticos legales que ayudaron a proporcionar con mayor facilidad la historia clínica del paciente; esto fue la solicitud dirigida al Hospital General Machala al Doctor Leonardo Alvarado subdirector médico, se presentó anteproyecto que enmarcaron el consentimiento informado. Como resultado se obtuvo que el paciente a través de la realización de diferentes estudios se establece el diagnóstico de Insuficiencia Renal Crónica. El paciente recibió como tratamiento de base: Simvastatina; Tamsulosina y Haloperidol. Concluimos que la Insuficiencia Renal Crónica es una de las patologías frecuentemente a nivel mundial según la OMS. En esta investigación de acuerdo al caso práctico el paciente presenta Insuficiencia Renal Crónica la cual afecta a la calidad de vida del individuo debido a que no se puede tener un buen manejo adecuado de su tratamiento; por estas razones se debe poner en marcha medidas de prevención. Los cambios que sufre el paciente diagnosticado de IRC son múltiples, entre ellos a nivel, familiar, social, personal y económico. Las intervenciones del personal de enfermería constituyen un pilar fundamental al momento de afrontar y aceptar situaciones precarias por la que pasa la paciente.
Keywords: INSUFICIENCIA RENAL CRONICA; GLOMERULONEFRITIS; HIPERTENSION ARTERIAL; DIABETES MELLITUS TIPO II